2017
DOI: 10.1073/pnas.1713320114
|View full text |Cite
|
Sign up to set email alerts
|

Properties of real metallic surfaces: Effects of density functional semilocality and van der Waals nonlocality

Abstract: We have computed the surface energies, work functions, and interlayer surface relaxations of clean (111), (110), and (100) surfaces of Al, Cu, Ru, Rh, Pd, Ag, Pt, and Au. Many of these metallic surfaces have technological or catalytic applications. We compare experimental reference values to those of a family of non-empirical semilocal density functionals from the basic local density approximation (LDA) to our most advanced, general-purpose meta-generalized gradient approximation, SCAN. The closest agreement w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

36
191
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(230 citation statements)
references
References 128 publications
36
191
0
3
Order By: Relevance
“…The WF of the clean surfaces are calculated to be 5.55 eV, 5.43 eV, and 5.60 eV for Au(100), Au(110), and Au(111), respectively. These values are in agreement with the previously reported LDA calculations [9,20,21]. As the top panel in Fig.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The WF of the clean surfaces are calculated to be 5.55 eV, 5.43 eV, and 5.60 eV for Au(100), Au(110), and Au(111), respectively. These values are in agreement with the previously reported LDA calculations [9,20,21]. As the top panel in Fig.…”
supporting
confidence: 93%
“…It has been shown that LDA DFT results more closely agree with experiment, because the LDA exchange energy contribution to the surface energy is overestimated, while the correlation contribution is significantly underestimated. These two errors nearly cancel each other [9]. For gold, the ultrasoft pseudopotential (USPP) was generated with the Rappe Rabe Kaxiras Joannopoulos (rrkjus) scheme with 11 valence electrons in a 5d 10 6s configuration.…”
mentioning
confidence: 99%
“…Our SCAN+rVV10 functional estimation of 5.45 eV for the clean gold surface is in good agreement with recent theoretical values. [83] The PBE functional, on the other hand, gives a value of 5.12 eV for Au(111). Graphene monolayer is estimated to have a work function of 4.58 eV and 4.48 eV with and without the vdW-corrections, respectively.…”
Section: B Electronic Structuresmentioning
confidence: 99%
“…With complex telescope systems (such as FAST, in which the surface of the dish and the focus cabin position continuously moves during a tracking observation) and new ultra-wide-band, or wide field-of-view, receivers new calibration procedures are becoming necessary. Novel calibration methods such as switching calibration signals at extremely high rates (Li, private communication), injecting pseudo-random-noise sequences, or short duration pulses (Patra et al 2017 are all currently being explored and we look forward to comparing these methods with the traditional calibration procedures in the near future. (24)…”
Section: In Summarymentioning
confidence: 99%